2016
DOI: 10.1007/s10867-016-9430-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hemin with quadruplex DNA

Abstract: A DNA enzyme with peroxidase activity is a G-quadruplex-based DNAzyme formed by hemin and G-quadruplex DNA. Activity of peroxide DNAzymes can be influenced by the structure of quadruplex DNA. In this investigation, the interaction of hemin with T30695 G-quadruplex DNA is evaluated. Molecular dynamic simulation indicates that the binding mode of hemin to G-quadruplex DNA is end-stacking, which is consistent with absorption spectroscopy. Based on fluorescence spectroscopy, hemin ejects thiazole orange from bases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Therefore, K + in general is preferred over Na + in G4 formation. Another study conducted also showed in the presence of KCl, the activity doubled that of NaCl [24].…”
Section: The Basic Structure Of G-quadruplexmentioning
confidence: 99%
“…Therefore, K + in general is preferred over Na + in G4 formation. Another study conducted also showed in the presence of KCl, the activity doubled that of NaCl [24].…”
Section: The Basic Structure Of G-quadruplexmentioning
confidence: 99%
“…This method has been used in much more studies as interaction of molecules and adsorption effects of different molecules and elements on the different surfaces [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Many authors also, in order to understand the biological and anticancer activity of certain drugs inevitably, have studied the physicochemical properties using DFT method [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Original Research Articlementioning
confidence: 99%
“…A DNAzyme with peroxidase activity is a well-known DNA enzyme and has been shown to adopt G-quadruplex structures. Hemin, a porphyrin, can non-covalently bind to the G-quadruplex which enhances the peroxidase activity of hemin (Kosman and Juskowiak, 2011;Ghahremani Nasab et al, 2017). This property of hemin conjugated to DNA quadruplex has been used as a strategy in screening ligands of Gquadruplex for a variety of applications which range from singlenucleotide polymorphisms to proteins and nucleic acids and also in drug discovery and diagnostics employing colorimetric or visual detection strategies and also as electrochemical sensors (Cheglakov et al, 2006;Cheng et al, 2009;Won et al, 2011;Bhadra et al, 2014;Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%